Consumption of the Soul: illness and travel in Gorriti - Aguila, Rocío del (2018)
In this essay I will analyze Laura, the main character from Peregrinaciones de una alma triste in order to discuss the process by which the agency of the feminine subject subverts the symbolic order. I will apply the concept of Pharmakon, as used by Jacques Derrida, on two different levels to show the complex relation between women patient and illness; and also to elucidate the situation of women while traveling and in exile.